2014
DOI: 10.1177/0363546514560729
|View full text |Cite
|
Sign up to set email alerts
|

Revision Versus Primary Arthroscopic Rotator Cuff Repair

Abstract: The short-term clinical outcomes of patients undergoing revision rotator cuff repair were similar to those after primary rotator cuff repair. However, these results did not persist, and by 2 years patients who had revision rotator cuff repair were twice as likely to have retorn compared with those undergoing primary repair. The increase in retear rate in the revision group at 2 years was associated with increased pain, impaired overhead function, less passive motion, weaker strength, and less overall satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 32 publications
3
84
0
2
Order By: Relevance
“…[53] One author operated on seven patients in a revision process and discovered modest development of feature. [54] Warner and Parsons had large decrease development of constant weighed rating, due especially to a much less significative ahead flexion development while lively external rotation and power have been not statistically unique among revision and primary sufferers. [55] Gerber et al located significative lower results for revision patients with postoperative fifty nine % regular weighed rating in comparison with 79percentfor primary sufferers, however, they noticed that boom of subjective shoulder price become similar in revision and in primary patients, (respectively, +37 % and +36 %) which supposed that revision patients may benefit from the procedure with the same quantity of subjective shoulder fee increase than number one patients despite the fact that starting from a decrease price.…”
Section: Current Conceptsmentioning
confidence: 94%
See 1 more Smart Citation
“…[53] One author operated on seven patients in a revision process and discovered modest development of feature. [54] Warner and Parsons had large decrease development of constant weighed rating, due especially to a much less significative ahead flexion development while lively external rotation and power have been not statistically unique among revision and primary sufferers. [55] Gerber et al located significative lower results for revision patients with postoperative fifty nine % regular weighed rating in comparison with 79percentfor primary sufferers, however, they noticed that boom of subjective shoulder price become similar in revision and in primary patients, (respectively, +37 % and +36 %) which supposed that revision patients may benefit from the procedure with the same quantity of subjective shoulder fee increase than number one patients despite the fact that starting from a decrease price.…”
Section: Current Conceptsmentioning
confidence: 94%
“…[68] Proximal migration of humeral head turned into also not unusual within the research in which this particular problem become searched for.1 study confirmed statistically significative progression of osteoarthritis handiest with combined switch of LD and TM tendons however in 87.5 % of the instances development turned into confined to at least one level in Hamada type. [47] Complications Some complications of the procedures have been describe: [2,15,25,43,54,69,70] • Hematoma.…”
Section: Current Conceptsmentioning
confidence: 99%
“…In addition, the intensity and type of daily activities could play a significant role; thus high re-tear rates have been observed in heavy worker groups [24, 25]. Revision surgery has probably higher possibility of failure than primary repair and is associated with increased pain, impaired overhead function, less passive motion, diminished strength, and less overall satisfaction with poorer overall shoulder function [26]. …”
Section: Factors Predicting Rotators Cuff Re-tear Ratementioning
confidence: 99%
“…4 Recurrent tears typically occur within the first six months following primary fixation. 5,6 Symptoms of re-tear at two years include: impaired overhead function, increased pain, limited passive movement, loss of strength, and lower overall satisfaction with shoulder function.…”
Section: Irreparable Posterosuperior Rctsmentioning
confidence: 99%
“…5,6 Symptoms of re-tear at two years include: impaired overhead function, increased pain, limited passive movement, loss of strength, and lower overall satisfaction with shoulder function. 4 Complications also arise when performing revision rotator cuff repairs. 7 Fortunately, when a posterosuperior RCT tear is deemed irreparable, there are several options for the patient.…”
Section: Irreparable Posterosuperior Rctsmentioning
confidence: 99%